Creativity, visualization abilities, and visual cognitive style. (19th March 2013) - Kozhevnikov, Maria; Kozhevnikov, Michael; Yu, Chen Jiao; Blazhenkova, Olesya
<x xml:space="preserve">Abstract</x> Background Despite the recent evidence for a multi‐component nature of both visual imagery and creativity, there have been no systematic studies on how the different dimensions of creativity and imagery might interrelate. Aims The main goal of this study was to investigate the relationship between different dimensions of creativity (artistic and scientific) and dimensions of visualization abilities and styles (object and spatial). In addition, we compared the contributions of object and spatial visualization abilities versus corresponding styles to scientific and artistic dimensions of creativity. Samples Twenty‐four undergraduate students (12 females) were recruited for the first study, and 75 additional participants (36 females) were recruited for an additional experiment. Method Participants were administered a number of object and spatial visualization abilities and style assessments as well as a number of artistic and scientific creativity tests. Results The results show that object visualization relates to artistic creativity and spatial visualization relates to scientific creativity, while both are distinct from verbal creativity. Furthermore, our findings demonstrate that style predicts corresponding dimension of creativity even after removing shared variance between style and visualization ability. The results suggest that styles might be a more ecologically valid construct in predicting real‐life creative behaviour, such as performance in different professional domains.